Die another day [videorecording (DVD)] - Wilson, Michael G., 1942-; Broccoli, Barbara, 1960-; Brosnan, Pierce; Berry, Halle; Cleese, John; Dench, Judi, 1934-; Fleming, Ian, 1908-1964 (MGM Home Entertainment, 2003)
While on assignment in North Korea, Bond is captured by government agents, where he's imprisoned and tortured for over a year. When Bond is exchanged for another prisoner, not everyone is certain 007 is still capable of doing the job. After an unscrupulous entrepreneur is discovered to be in cohoots with the other prisoner, Bond is back on the case, and he finds the two men have sinister plans which could decide the fate of the world.